Relationship of Resilience and Social Support with Burnout on Intelmob - Maulidya, Novarida; Noviekayati, IGAA; Evita Santi, Dyan (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study aims to determine the relationship between resilience and social support with burnout in Intelmob, as well as analyze between each independent variable (resilience and social support) and burnout in Intelmob. This study uses a quantitative approach with a correlational design, on 86 East Java Intelmob personnel who were selected through a saturation sampling technique. The data was gathered by use of a Likert scale.. The study tools included a burnout scale, a resilience scale, and a social support scale, all of which were evaluated for validity and reliability using SPSS 27.0 for Windows software. The data was then evaluated by multiple linear regression analysis. The results showed that resilience and social support had a significant negative relationship with burnout in Intelmob personnel. Which indicates that the higher the resilience and social support, the lower the burnout rate experienced. Where resilience helps individuals manage work stress, while social support plays a role in emotional protection. These two factors together account for 28.7% of the variability in burnout, whereas the remainder is affected by other variables. Intelmob employees' resilience and social support systems are key to lowering burnout rates; as a result, the company needs better policies and procedures to help employees' mental health and boost their productivity.